SPE Reservoir Simulation Symposium 2005
DOI: 10.2118/93053-ms
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Fracture Network Modeling of Naturally Fractured Reservoirs

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThis paper provides a review of common approaches for simulation of naturally fractured reservoirs and a new model formulation that is more amenable to the utilization of detailed geologic information from deterministic models, multipoint statistical simulations (MPS), and discrete fracture network (DFN) models. Unlike the common dual-porosity and dualpermeability models, the new model considers flow in several sets of fractures (that is, micro, macro, and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Our approach (Yetkin, 2007) for an isotropic reservoir reduces to the classical 9-point finite-difference (Smith, 1978) with the discretization error of O (Δx 6 ). Furthermore, in our 13-point discretization, we used a square reservoir with no-flow outer boundary conditions instead of an infinite reservoir used by Bagheri and Settari. Another method to account for the permeability tensor is constructing a 2-D octagonal perpendicular bisector (PEBI) grid from a conventional 2-D Cartesian grid (Kazemi, 1992, Chong et el., 2004, and Kazemi et al, 2005 as shown in Figs. 3 and 4.…”
Section: Background and Literature Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…Our approach (Yetkin, 2007) for an isotropic reservoir reduces to the classical 9-point finite-difference (Smith, 1978) with the discretization error of O (Δx 6 ). Furthermore, in our 13-point discretization, we used a square reservoir with no-flow outer boundary conditions instead of an infinite reservoir used by Bagheri and Settari. Another method to account for the permeability tensor is constructing a 2-D octagonal perpendicular bisector (PEBI) grid from a conventional 2-D Cartesian grid (Kazemi, 1992, Chong et el., 2004, and Kazemi et al, 2005 as shown in Figs. 3 and 4.…”
Section: Background and Literature Reviewmentioning
confidence: 95%
“…Chong et al (2004) successfully used this grid to reduce grid orientation effects in a quarter of a five-spot homogeneous isotropic waterflood simulation. Kazemi, et al (2005) proposed this construction to account for permeability anisotropy in naturally fractured reservoirs.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…The DFN approach has widely been used in modelling fractures (e.g. [32,33,34,35,36]), which is appropriate for well scale modelling [37]. The fracture sub-sets have honoured detailed geological observations of the outcrop [9].…”
Section: Fracture Permeabilitymentioning
confidence: 99%
“…The illustrated fracture pattern in Figure 2 (the red part), was imported into a geological modelling package and a fracture network was created deterministically in the model. The discrete fracture networks (DFN) approach was used, which is appropriate for well scale or sector modelling [5,6,26,27,28,29]. This work aims to investigate the effect of contact areas and fracture surface roughness on effective fracture permeability.…”
Section: D Simulation Modelsmentioning
confidence: 99%